The Pronunciation of English Speech Sounds in Speaking Classes Among the Eleventh Graders of Senior High School Randudongkal Pemalang - Anis Ardiana Mumtaza; Januarius Mujianto; Hendi Pratama (Universitas Islam Negeri Palopo, 2025)
This study aims to describe the students' pronunciation in English speech sounds among eleventh grade students at SMA Negeri 1 Randudongkal. The purpose of this study explores more deeply how challenges are encountered by students to speak English, specifically concerning pronunciation. Pronunciation is one of the most challenging skills for students to master, primarily because many lack enough interest or motivation to acquire English. The lack of interest not only blocks language progress, but also affects students' confidence and readiness to use English. The approach to this research follows a descriptive qualitative approach to provide finding related to translation outputs. Within this approach, a focus lies between a personal interpretation of reality to portray phenomena, according to a given theoretical approach guiding the researcher's point of view. In involving data collection through a test and record. The current study uses several methods, including observing classroom atmosphere and evaluating student engagement within English classes. A very strong focus lies in enhancing students' speaking skills, with a focus point concerning English pronunciation in order to evaluate said points, this research seeks to get a clearer understanding concerning students' pronunciation skills, to identify areas where speaking skills can be enhanced. The findings from this research are expected to uncover certain difficulties being encountered by students with English pronunciation, in order to enable them better to understand spoken English. Through simulating students' pronunciation analysis and examining the made sound, this research aims at identifying particular words sound causing difficulties in comprehending spoken English. The study also intends to assist students in enhancing English pronunciation by practicing accurate and clear reading from texts